Perceptions of participants of management development programmes in the Gauteng Health Department. - Bassed, Philistas Jane (My University, 2003)
Management development has been identified as one of the priorities in the Gauteng Health Department [GHD]. The nature of public service management is changing. There is an emphasis on new and more flexible management approaches in the public sector; this requires public service managers to acquire new kinds of skills. Further to this, the changing nature of management in general, caused by globalization increases the need for new kinds of skills amongst managers. This changing framework is facilitated by various new laws, which provide a watershed in the way that human resource development is undertaken in South Africa. It is necessary to ensure that training and development initiatives in the Department are aligned to the new legislative framework. The Employment Equity Act requires representivity in the workplace; there is a need for management skills development programmes to redress past imbalances. The GHD provides several management development programmes for its employees every year. In keeping with current trends and legislation it is necessary to evaluate these programmes to identify strengths and weaknesses in order to improve future management development programmes in the GHD, and ensure that money is well spent. The main goal of this research is to formulate guidelines for the effective implementation of management development programmes in the GHD. The objective of the study is to explore and describe the perceptions of the participants of management development programmes provided by the Department between 1999 and 2001. The researcher used focus groups for data collection and individual interviews for methodological triangulation. The population (N) in this study comprises of all the people who attended management development programme/s purchased by the Department between 1999 and 2001. Three Hundred and forty eight managers attended the programmes between 1999 to 2001 (N = 348).Purposive samples were used for the focus groups and individual interviews. An independent interviewer was used to conduct the interviews in order to ensure objectivity, and anonymity of the participants. Fields notes were taken and the interviews audio-recorded. Written consent was obtained from the participants for the audio recording of the interviews. The data were transcribed verbatim. The Tesch method was employed to analyse the data. The data were grouped and coded. Emerging themes and sub-themes were identified and contextualised through a literature control. Scrutiny of the study by the Ethics Committee of the University of the Witwatersrand ensured ethical rigor. The findings were used to formulate guidelines for future management development programmes in the GHD. The research report was communicated to the GHD.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand in partial fulfillment of the requirements for the degree of Master of Science (Nursing)
Keywords: Nursing; Program Development; Staff Development